Analysis of Employment Attitude to Musculoskeletal Complaints on Operators of Public Fuel Filling Station (SPBU) In Palembang City, 2021 - Alq'na Miftasyah; Novrikasari Novrikasari; Hamzah Hasyim (Budapest International Research and Critics University, 2022)
Musculoskeletal Disorders (MSDs) are disorders of the musculoskeletal system that cause symptoms such as pain due to damage to nerves and blood vessels in various locations of the body such as the neck, shoulders, wrists, hips, knees, and heels. This condition causes workers to experience fatigue more quickly. This study aims to analyze work attitudes towards complaints of Musculoskeletal Disorders at gas station operators in Palembang City. This type of research is a cross sectional study. The research was conducted at 12 gas stations in Palembang City. The number of samples in the study were 121 operators. Data was collected using interview techniques and data collection instruments using a questionnaire measuring instrument Nordic Body Map (NBM), and Rapid Entire Body Assessment (REBA). The results showed that there was a relationship between age and complaints of Musculoskeletal Disorders (p-value = 0.000), gender (p-value = 0.023), years of service (p-value = 0.000), smoking habits (p-value = 0.000), activity physical (p-value = 0.000), and work attitude (p-value = 0.000). Gas station workers are expected to be able to do light body stretching between breaks so as to reduce the risk of Musculoskeletal Disorders. Gas station operators are also expected to pay more attention to their work attitude, because if they do work with a bad work attitude, it will speed up the process of musculoskeletal disorders complaints.Keywords: Musculoskeletal Disorder (MSDs), Ergonomic, Gas Station